Comparison of Holmium: Yttrium Aluminum Garnet laser with pneumatic lithotripsy in the treatment of ureteric stones by semi-rigid ureteroscope - Islam, Md Shahinur; Alam, Md Shawkat; Islam, Md Faisal; Alam, Md Rashedul; Zumma, Asif Md Sazzad Uz; Munir, Serajum (Bangladesh Journal of Urology, 2025)
Background: Ureteric calculi are one of the major causes of attendance at emergency and outpatient department in urology. Miniaturization of endoscopic devices has revolutionized the management of ureteric calculi. Ureteric calculi are effectively managed by semi-rigid URS. Holmium: YAG laser and pneumatic lithotripsy are two most efficacious and widely used intra-corporeal lithotripsy device. Objective: To compare the efficacy of Holmium: YAG laser with pneumatic lithotripsy in the treatment of ureteric stones by semi-rigid ureteroscope. Methodology: A total of 70 adult patients were selected by purposive sampling technique and divided into laser lithotripsy (LL) group and pneumatic lithotripsy (PL) group by lottery. Test of significance was independent sample t-test for quantitative outcome and Chi-square (X2) test or Fisher’s exact test for categorical outcome. P- value of less than 0.05 was considered significant and 95% confidence interval was used. Result: Two groups were similar in age, gender, mean size of stones and side of stones. There was a statistical difference in terms of stone clearance, stone migration and mean hospital stay in favor of the LL group (P = 0.035, P = 0.024 and P = 0.002 respectively), and mean operating time in favor of the PL group (P = 0.034). A statistically significant (p=0.044) more post-operative hematuria was found in PL group. There was no significant difference in mucosal injury, ureteral perforation and post-operative fever in both groups. Conclusion: Holmium: YAG laser lithotripsy is more efficacious than pneumatic lithotripsy in terms of rate of stone clearance, complications and post-operative hospital stay while the mean operating time is significantly shorter in PL group. Bangladesh J. Urol. 2024; 27(2): 132-136